Commercialization of the football industry: what unites and distinguishes international and Russian football organizations in entrepreneurial activity - M. Yu. Krasnova (Путеводитель предпринимателя)
The article examines the similarities and different entrepreneurial activities carried out by Russian and foreign football organizations. The relevance of the topic under consideration deals with the fact that in modern conditions the commercialization of football acts as a necessary factor in the promotion of this sport throughout the world. The main methods used in the work are analytical and comparative–comparative methods.The author, in the process of research, explains why international competitions are constantly growing, and the growth rate is constantly increasing. And also according to the results of the study, it was concluded: in Russia, the commercialization of football is at an early stage, and the solution to this problem is quite distant prospects.